2023
DOI: 10.3390/plants12030600
|View full text |Cite
|
Sign up to set email alerts
|

Response of Maize Varieties (Zea mays L.) to the Application of Classic and Stabilized Nitrogen Fertilizers—Nitrogen as a Predictor of Generative Yield

Abstract: The study presents the results of a 3-year field trial aimed at assessing the yield and efficiency indicators of nitrogen application in the cultivation of three maize cultivars differing in agronomic and genetic profile. The advantages of the UltraGrain stabilo formulation (NBPT and NPPT) over ammonium nitrate and urea are apparent if a maize cultivar capable of efficient nutrient uptake in the pre-flowering period and effective utilization during the grain filling stage is selected. Therefore, the rational f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Similar to those of a large number of solid fertilizer experiments, our results showed that the addition of a UI to liquid fertilizer can effectively inhibitt the NH 3 emission, but adding an NI increased the NH 3 emission [ 34 ]. In a short time, the single application of UI only delayed the time of the formation of volatile ammonia, but cannot reduce the total ammonia emission loss [ 35 , 36 , 37 ]. Only by combining two types of inhibitors and exerting their synergistic effects can the whole process of urea N conversion in the soil be effectively adjusted, thereby reducing the loss of urea N by various pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to those of a large number of solid fertilizer experiments, our results showed that the addition of a UI to liquid fertilizer can effectively inhibitt the NH 3 emission, but adding an NI increased the NH 3 emission [ 34 ]. In a short time, the single application of UI only delayed the time of the formation of volatile ammonia, but cannot reduce the total ammonia emission loss [ 35 , 36 , 37 ]. Only by combining two types of inhibitors and exerting their synergistic effects can the whole process of urea N conversion in the soil be effectively adjusted, thereby reducing the loss of urea N by various pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors such as temperature and moisture also affect the availability of macro- and micronutrients [ 31 ]. Studies conducted in the corn belt of the USA [ 13 , 32 ], tropical regions [ 33 , 34 ], and Europe [ 27 , 35 , 36 , 37 ] show that genotypes can differ significantly in the level of N utilization. Some authors believe that in the period before flowering, there is competition between the reproductive and vegetative organs in assimilative uptake and that their accumulation in the grain depends on the amount of accumulated assimilative [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in soil moisture below the minimum range limit from the formation of the eighth leaf has a negative effect on the grain yield [60,61], depending more or less on the duration of the drought period. Undoubtedly, the rainfall factor is a major element in the cultivation of maize [62,63], especially if the rainfall level is defective during certain years or during certain stages of the vegetation period [64]. Moderate moisture from the appearance of the eighth leaf to tillering and from drought to tillering cuts maize yield in half [65].…”
Section: Discussionmentioning
confidence: 99%